Improving Training Condition Assessment in Endurance Cyclists: Effects of Ganoderma lucidum and Ophiocordyceps sinensis Dietary Supplementation. (1st April 2014) - Rossi, Paola; Buonocore, Daniela; Altobelli, Elisa; Brandalise, Federico; Cesaroni, Valentina; Iozzi, Davide; Savino, Elena; Marzatico, Fulvio
Abstract : The main reasons for taking daily dietary supplements are to maintain good health, to improve homeostasis, and to create conditions for reducing the risk of disease. Due to growing market demand, the search for effective, nontoxic, natural compounds with antioxidant and ergogenic properties has increasingly become a matter of interest. This paper describes how a specific combination of fungal supplements can help improve the performance of endurance athletes. We report the effects of a brief 3-month trial of two fungal supplements, Ganoderma lucidum and Cordyceps sinensis (3 capsules of O. sinensis and 2 capsules of G. lucidum per day), in 7 healthy male volunteers, aged between 30 and 40 years, who are all amateur cyclists that participate in "Gran Fondo" cycling races. This trial investigated the effects of fungal supplements on the level of physical fitness of the athletes by monitoring and comparing the following biomarkers just before and after physical exertion: the testosterone/cortisol ratio in the saliva and oxidative stress (DPPH free radical scavenging activity). A decrease of more than 30% in the testosterone/cortisol ratio after race compared to before race was considered as a risk factor for nonfunctional overreaching (NFO) or the overtraining syndrome (OTS). The results show that, after 3 months of supplementation, the testosterone/cortisol ratio changed in a statistically significant manner, thereby protecting the athletes from NFO and OTS. Antioxidant activity was measured by quantifying the scavenging ability of the human serum on the synthetic free radical DPPH. After 3 months of fungal supplementation, the data demonstrate an increased scavenger capacity of free radicals in the athletes' serum after the race, thereby protecting the athletes from oxidative stress.